Determination of [function]s/[function]d for 7 TeV pp collisions and measurement of the B0→D-K+ branching fraction - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; et al. (Physical review letters, 2011)
The relative abundance of the three decay modes B0→D−K+, B0→D−π+, and B0s→D−sπ+ produced in 7 TeV pp collisions at the LHC is determined from data corresponding to an integrated luminosity of 35 pb−1. The branching fraction of B0→D−K+ is found to be B(B0→D−K+)=(2.01±0.18stat±0.14syst)×10−4. The ratio of fragmentation fractions fs/fd is determined through the relative abundance of B0s→D−sπ+ to B0→D−K+ and B0→D−π+, leading to fs/fd=0.253±0.017±0.017±0.020, where the uncertainties are statistical, systematic, and theoretical, respectively.
*LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, K. Holubyev, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und 531 weitere Personen]
Im Titel ist "function" als mathematisches Zeichen dargestellt
Im Titel sind die Zahl 0 sowie die Zeichen - und + hochgestellt
Gesehen am 14.02.2022